Exogenous Tracheal Bone Structure in a Cat - Caramalac, Simone Marques; Caramalac, Silvana Marques; Jardim, Paulo Henrique Affonseca; Frazilio, Fabrício de Oliveira; Palumbo, Mariana Isa Poci (Acta Scientiae Veterinariae, 2021)
Background: Acute dyspnea is a clinical emergency with a presentation similar to several etiologies. Cats are usually referred with complaints of anorexia, abdominal breathing, cyanosis, and open mouth breathing, and veterinarians should stabilize the animals as soon as possible. The incidence of aspiration of foreign bodies is low, particularly in this species. The diagnosis consists of observing the foreign structure in the lumen of the trachea, commonly performed using radiography or bronchoscopy. This report describes a case of a feline with a tracheal foreign body, with a detailed description of the clinical findings and successful treatment. Case: A 10-year-old female feline exhibited severe dyspnea and cyanosis. During the anamnesis, the owner stated that the clinical signs suddenly presented one day prior, after the animal ingested a piece of fish. Physical examination revealed changes in pulmonary auscultation, which was bilaterally muffled, and intense respiratory distress, as observed by the evident signs of exhaustion (sternal decubitus, reduced muscle tone), in addition to cyanotic mucous membranes. The animal was intubated and maintained under anesthesia with propofol infusion and respiratory support (ambu) for 1 h, during which complementary examinations were performed. Chest radiography showed the presence of a radiopaque structure (approximately 0.5 cm) in the tracheal region. Thus, we decided to remove the structure using bronchoscopy. The foreign body was located above the main bronchial bifurcation and was removed. There was an improvement in oxygenation after 20 min of maintenance of ventilatory support, followed by weaning of the animal's successful respiratory support. Antibiotic therapy and analgesia were prescribed at home, and the animal exhibited full recovery after 10 days. Discussion: Dyspnea is a clinical sign that should be treated as an emergency, as it is associated with high mortality. In these cases, positive pressure ventilation is indicated in three situations: persistent hypoventilation, severe hypoxemia unresponsive to oxygen therapy, and excessive respiratory effort or fatigue. Dyspnea may be due to impairment of the upper or lower airway or restrictive conditions. Clinically, felines with tracheal foreign bodies have a sudden onset of dyspnea, tachypnea, cough, and lethargy. In these patients, the reduction in lung sounds is a common finding, as observed in the present case. The occurrence of tracheal foreign bodies in cats is rare and, depending on the type of foreign body and its location in the airway, complete obstruction of the respiratory tract may occur. In the present case, it was possible to observe the foreign body in the trachea on radiographic images. Felines with tracheal foreign bodies generally present a structure located close to the carina, as observed in the present case. Bronchoscopy using a flexible or rigid tube is considered the gold-standard technique for removing foreign bodies from the respiratory tract, and the greatest difficulty during the removal procedure is ensuring that the airways are not obstructed by the instruments used. The use of these materials is not free of complications, as they may be responsible for the development of pneumothorax, pneumomediastinum, dyspnea, and respiratory failure. In the present case, there were no complications during or after the procedure, and the patient recovered completely.